ISLAMIC ECOTEOLOGICAL VALUES IN FIKIH LEARNING: CONSTRUCTION OF ECOLOGICAL AWARENESS OF MADRASAH ALIYAH STUDENTS - Anggraini, Anggi; Zuhri; Sutiah; Samsul Susilawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of Islamic ecotheological values on students’ ecological awareness in fiqh learning at MAN 4 Pekanbaru City. The ecological crisis occurring today indicates the low level of environmental awareness among society, including students in Islamic educational institutions. In fiqh learning, ecological values are often taught theoretically and have not been fully integrated into students’ daily behavior. This research employed a quantitative approach with an explanatory design. The sample consisted of 120 students selected using proportionate stratified random sampling. Data were collected through a closed-ended questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The variables examined in this study were Islamic ecotheological values as the independent variable and students’ ecological awareness as the dependent variable. The findings revealed that Islamic ecotheological values have a positive and significant effect on students’ ecological awareness, with a p-value of 0.032 (< 0.05). The results indicate that the internalization of Islamic values such as khalīfah fī al-ardh, amanah, mīzān, and the prohibition of environmental destruction contributes significantly to the development of students’ ecological behavior. Furthermore, fiqh learning integrated with Islamic ecotheological values encourages students to conserve water, maintain cleanliness, manage waste responsibly, and demonstrate greater concern for environmental sustainability. Therefore, integrating Islamic ecotheology into fiqh learning can serve as an effective strategy for strengthening ecological awareness and environmental responsibility among madrasah students. Keywords: Islamic Ecotheology Values, Ecological Awareness, Fikih Learning, Environmental Education